Presidential Decree-Law No. 82 of the Year 2013 On Amending Certain Provisions of the Issuing Articles of Law No. 89 of the Year 1998 On Organizing Tenders and Bids and Some Provisions of the Said Law = قرار رئيس جمهورية مصر العربية بالقانون رقم 82 لسنة 2013 في شأن تعديل أحكام القانون رقم 89 لسنة 1998 بإصدار قانون تنظيم المناقصات والمزايدات وبعض أحكام قانون تنظيم المناقصات والمزايدات / presidency - Egypt. presidency (2025)
Presidential Decree-Law No. 82 of the Year 2013 On Amending Certain Provisions of the Issuing Articles of Law No. 89 of the Year 1998 On Organizing Tenders and Bids and Some Provisions of the Said Law قرار رئيس جمهورية مصر العربية بالقانون رقم 82 لسنة 2013 في شأن تعديل أحكام القانون رقم 89 لسنة 1998 بإصدار قانون تنظيم المناقصات والمزايدات وبعض أحكام قانون تنظيم المناقصات والمزايدات